2018
DOI: 10.24099/vet.arhiv.170613a
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of Genogroup 5 Rotavirus associated with piglet diarrhoea in the North East Region of India

Abstract: Rotaviruses have been recognized as an important etiological agent of non-bacterial acute gastroenteritis in young children and animals of several species worldwide, including diarrhoea in weaning and post-weaning piglets. In this study, we report the prevalence and molecular epidemiology of rotaviruses detected from piglets in different regions of the northeastern hilly region of India. A total of 457 faecal samples (339 diarrhoeal and 118 non-diarrhoeal) were collected from piglets from local (n = 130) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…Detection of Salmonella by real-time PCR The result of RT-PCR detection of salmonella showed that the salmonella was detected in 8 (8%) out of 100(100%) stool specimens that collected from patient with acute diarrhea. this result matched to fi ndings of Kylla et al 13 that show A total of 8.31% Salmonella were identifi ed with higher prevalence. Also, another study showed that the prevalence of Salmonella isolates was 6.9% Children aged between 1 to 3 years were test for all positive RT-PCR stool samples.…”
Section: The Results Of Rt-pcr Detection Of Campylobactersupporting
confidence: 90%
“…Detection of Salmonella by real-time PCR The result of RT-PCR detection of salmonella showed that the salmonella was detected in 8 (8%) out of 100(100%) stool specimens that collected from patient with acute diarrhea. this result matched to fi ndings of Kylla et al 13 that show A total of 8.31% Salmonella were identifi ed with higher prevalence. Also, another study showed that the prevalence of Salmonella isolates was 6.9% Children aged between 1 to 3 years were test for all positive RT-PCR stool samples.…”
Section: The Results Of Rt-pcr Detection Of Campylobactersupporting
confidence: 90%
“…Lack of scientific literature regarding the prevalence of EPEC; prevented us from comparing our results to precedents. However, similar findings were reported in a prevalence study of diarrhoeagenic bacterial and viral pathogens ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 89%
“…Many researchers [38][39][40][41] reported that RVA is the most common cause of viral diarrhea in neonatal pigs compared to Type C, and other workers have detected porcine Rotavirus in diarrheic fecal samples in nursing, weaning, and post-weaning pigs either alone or in combination of other enteric pathogens such as E. coli, Salmonella, and Adenovirus [42,43]. Rotavirus A is only often detected as the sole infectious agent than as coinfection in cases of neonatal diarrhea [31,44].…”
Section: Discussionmentioning
confidence: 99%